Pengaruh E-Service Quality Dan Customer Perceived Value Terhadap Customer Satisfaction Dengan Trust Sebagai Variabel Mediasi Pada Transportasi Grab (Studi Kasus Pada Pengguna Grab Di Kota Yogyakarta) - Mutiara, Thoriq Abdillah; Nyoman Udayana, Ida Bagus; Diansepti Maharani, Bernadetta (Universitas Hamzanwadi, 2024)
This study aims to determine (1) The effect of E-Service Quality on Customer Satisfaction (2) The effect of Customer Perceived Value on Customer Satisfaction (3) The effect of E-Service Quality on Trust (4) The effect of Customer Perceived Value on Trust (5) The effect of Trust on Customer satisfaction. The sample in this study were 105 respondents from the people of Yogyakarta City who had used Grab Transportation. The data collection method uses a questionnaire method which is distributed using purposive sampling technique. This study uses Data Quality Test, Classical Assumption Test, Multiple Regression Test and Hypothesis Test. The results of this study indicate (1) there is a positive and significant effect of E-Service Quality on Customer Satisfaction (2) there is a positive and significant effect of Customer Perceived Value on Customer Satisfaction (3) there is a positive and significant effect of E-Service Quality on Trust (4) there is a positive and significant effect of Customer Perceived Value on Trust (5) there is no positive and significant effect of Trust on Customer Satisfaction.